Investigation And Control of Scabies in Shelter Homes of Mandya City - Poornima Sadashivaiah; Raghini Ranganathan; Vinay M; Shreedhara Chikkade; B J Mahendra (Medsci Publications, 2013)
Two children with scabies and impetiginisation were admitted to Mandya institute of Medical Sciences (MIMS). Epidemiological investigation revealed that these children were traced to a common childcare facility in Mandya City. Cluster testing of the children from different childcare facilities led to identification of 38 cases of scabies. Blanket treatment was initiated with Lindane lotion and the children were monitored. This outbreak investigation explains how cluster testing led to diagnosing, treatment, control and prevention of scabies in the child care facilities.